2018
DOI: 10.1038/s41431-017-0082-2
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and molecular characterisation of CRB1-associated maculopathy

Abstract: To date, over 150 disease-associated variants in CRB1 have been described, resulting in a range of retinal disease phenotypes including Leber congenital amaurosis and retinitis pigmentosa. Despite this, no genotype–phenotype correlations are currently recognised. We performed a retrospective review of electronic patient records to identify patients with macular dystrophy due to bi-allelic variants in CRB1. In total, seven unrelated individuals were identified. The median age at presentation was 21 years, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 41 publications
2
60
0
Order By: Relevance
“…One of the main working hypothesis that we draw from our four CRB1-LCA-like models is that CRB2 protein levels may be lower or that a less functional variant is of CRB2 is expressed in CRB1 LCA patients compared to less severe CRB1 retinal diseases [132,298,299]. Clinical reports of CRB1 LCA patients have shown that degeneration can affect all quadrants of the retina while other reports show restriction to the inferior retina [285,288,300,301]. This is highly suggestive of the presence of a modifying factor.…”
Section: Crb1 and Leber Congenital Amaurosismentioning
confidence: 99%
“…One of the main working hypothesis that we draw from our four CRB1-LCA-like models is that CRB2 protein levels may be lower or that a less functional variant is of CRB2 is expressed in CRB1 LCA patients compared to less severe CRB1 retinal diseases [132,298,299]. Clinical reports of CRB1 LCA patients have shown that degeneration can affect all quadrants of the retina while other reports show restriction to the inferior retina [285,288,300,301]. This is highly suggestive of the presence of a modifying factor.…”
Section: Crb1 and Leber Congenital Amaurosismentioning
confidence: 99%
“…These disease characteristics resemble pathologies observed in human macular telangiectasia type 2 (MacTel 2). 30 Over 150 CRB1 alleles 31 have also been reported to cause a multitude of human retinal diseases. CRB1 variants are associated with retinal degenerative phenotypes ranging from Leber congenital amaurosis 8 (MIM# 613835), characterized by congenital or early-onset blindness, to retinitis pigmentosa (RP12, MIM# 600105), a more slowly progressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although null mutations appear to be overrepresented in LCA patients carrying CRB1 mutations, 32 attempts to correlate the CRB1 genotype with unique disease features have not been successful; perhaps the range of disease phenotypes observed is a consequence of interactions with additional genetic and/or environmental factors. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…All eyes with CME had abnormal cone ERGs. Although cones are densely packed in the macula (Osterberg 1935;Jonas et al 1992), macular dysfunction alone contributes only minimally to the full-field cone (Dawson & Maida 1984;Khan et al 2018;Robson et al 2018). The abnormal ERG in the children with CME therefore indicates a global retinal dysfunction and not only macular dysfunction .…”
Section: Discussionmentioning
confidence: 99%